Improving the Quality of Education Management Through Training and Guidance at a Private Tsanawiyah Madrasah - Mansur (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
his research aims to improve the quality of education management through training and guidance at Private Tsanawiyah Madrasas. The activity was carried out online through the Zoom application, involving 30 educators from Private Tsanawiyah Madrasah. Training materials cover education management concepts, classroom management strategies, and the use of technology in learning. In addition, group discussions and case studies are applied to stimulate collaboration and exchange of ideas. The results showed a significant improvement in participants' knowledge and skills. The implementation of best practices, collaboration between madrassas, and the use of technology are evidence of success. Positive feedback from stakeholders confirms the positive impact on the quality of education at the Madrasah Tsanawiyah level. Suggestions for further activities are to conduct long-term monitoring of the implementation of practices, as well as exploring the impact of education management on student learning outcomes. Financial support from relevant agencies contributes significantly to the success of this activity.